Assessing the Efficacy of Lopinavir/Ritonavir-Based Preferred and Alternative Second-Line Regimens in HIV-Infected Patients: A Meta-Analysis of Key Evidence to Support WHO Recommendations - Huang, Yinqiu; Huang, Xiaojie; Luo, Yadong; Zhou, Yihong; Tao, Xingbao; Chen, Hui; Song, Aixin; Chen, Yaokai; Wu, Hao (Frontiers in Pharmacology, 2018)
Background: Include nucleoside reverse-transcriptase inhibitors (NRTIs) and non-NRTIs (NNRTIs) with boosted protease inhibitors were included in standardized first-line and second-line regimens. Recent WHO guidelines recommend a boosted protease inhibitor (PI) combined with 2NRTIs or raltegravir as a second-line regimen. Object: Ritonavir-boosted lopinavir (LPV/r) is known as a key second-line antiretroviral therapy (ART) in resource-limited settings. We carried out a meta-analysis in order to analyze virologic suppression and effectiveness of LPV/r-based second-line therapy in HIV-infected patients. Methods: In this meta-analysis, we searched randomized controlled trials and observational cohort studies to evaluate outcomes of second-line ART for patients with HIV who failed first-line therapy. A systematic search was conducted in Pubmed, Cochrane Library, and Embase from inception to January 2018. Outcomes included viral suppression, CD4 cell counts, drug resistance, adverse events and self-reported adherence. We assessed comparative efficacy and safety in a meta-analysis. Data analysis was performed using RevMan 5.3 and Stata12.0. Results: Nine studies comprising 3923 patients were included in the meta-analysis. The overall successful virologic suppression rate of the second-line regimen was 77% (ITT) and 87% (PP) in 48 weeks with a plasma HIV RNA load < 400 copies/mL. No statistical significance was found in CD4 cell count recoveries between LPV/r plus 2-3 NRTIs and simplified regimens (LPV/r plus raltegravir) at 48 weeks (P=0.09), 96 weeks (p=0.05) and 144 weeks (P=0.73). Four studies indicated that the virus had low-level resistance to LPV/r, and the most common clinically significant PI-resistance mutations were 46I, 54V, 82A/82F and 76V; however, no virologic failure due to LPV/r resistance was detected. In addition, no statistical significance was found between the two groups in self-reported adherence (RR=1.03,95% CI 1.00, 1.07, P=0.06), grade 3 or 4 adverse events (RR=0.84，95% CI 0.64, 1.10, P=0.20) and serious events (RR=0.85, 95% CI 0.77, 1.17, P=0.62). Conclusions: These results suggested that the LPV/r-based regimen demonstrated efficacious and low resistance as second-line antiretroviral therapy. LPV/r plus 2-3 NRTIs and LPV/r plus RAL regimens both improved CD4 cell counts. There was no evidence of superiority of simplified regimens over LPV/r plus 2-3 NRTIs.